Critical Discourse Analysis News Coverage on The Palestina-Israeli Conflict: An Indonesia Media Perspective - Saraswati, Putu Isma; Pramiyanti, Alila (Universitas Pendidikan Ganesha, 2025)
This research analyses the coverage of the Palestinian-Israeli conflict in Indonesia's national online media. Media has an important role in advocacy and shaping public opinion in a conflict event. Peace journalism is a means of advocacy that the media can use to help the peace process by presenting news articles that do not favour certain groups and provoke one of the actors in the conflict. Using Teun Van Dijk's critical discourse analysis, which involves three main aspects: text, social cognition, and social context, how discourse is produced can be seen. The results of this study show that the writer’s background will affect the production of news texts, which can be seen from the writing style and experience while working in the media. External pressure from the government, audience, and advertisers causes the discourse produced by the media to be unconsciously affected by the ideology of the ruling group. The importance of applying peace journalism in news coverage can contribute to resolving conflicts and reducing tensions between the actors involved.